Separation of eight phenolic compounds from the over-ground parts of Aconitum pendulum Busch by repeated injection high-speed counter-current chromatography. Issue 10 (3rd July 2022) - Chen, Tao; Liu, Yongling; Wang, Shuo; Wei, Yangfei; Song, Zhibo; Yan, Shuping; Shen, Cheng; Li, Hongmei; Li, Peipei; Li, Yulin
ABSTRACT: In this study, eight phenolic compounds were obtained from the over-ground parts of the Aconitum pendulum ( A. pendulum ) Busch through an efficient high-speed counter-current chromatography （HSCCC）method. First, the column chromatography for macroporous resin was used for the treatment of crude extract of over-ground parts of A. pendulum Busch. And then, 30% ethanol elution fraction was transferred to HSCCC for separation using the classic ethyl acetate, n-butanol and water system with the solvent ratio of 7:3:10. To improve parting efficiency, a mode of repeated injection was developed. Two groups of compounds existing in one HPLC peak were effectively separated by HSCCC. The results revealed that HSCCC could effectively isolate compounds with the same or similar polarity. Preparative HPLC was used to perform further purification, and then eight phenolic compounds were separated from the over-ground parts of the A. pendulum Busch for the first time. The current investigation successfully provides a reference for phytochemical research and, comprehensive development and utilization of A. pendulum Busch in the future. Furthermore, HSCCC efficiently separated compounds with similar polarity and its combination with preparative HPLC could play a great role in the separation of natural materials.